2004
DOI: 10.1038/oby.2004.138
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Dysfunction in Morbidly Obese Women: Pilot Study

Abstract: KAPOOR, DHARMESH S., G. WILLY DAVILA, RAUL J. ROSENTHAL, AND GAMAL M. GHONIEM. Pelvic floor dysfunction in morbidly obese women: pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 15 publications
1
28
1
3
Order By: Relevance
“…Multivariable logistic regression analyses were performed to assess the interaction of covariables on the risk for anal incontinence symptoms. Selection of co-variables tried in the multivariable model was based on factors associated with anal incontinence in existing literature, including body mass index [12,13], overall parity [16], instrumental deliveries [17], obstetrical anal sphincter injury [18], smoking [19], menopausal status [9] and depression [20]. We also added variables with a significant association to anal incontinence symptoms at univariable analysis to the multivariable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable logistic regression analyses were performed to assess the interaction of covariables on the risk for anal incontinence symptoms. Selection of co-variables tried in the multivariable model was based on factors associated with anal incontinence in existing literature, including body mass index [12,13], overall parity [16], instrumental deliveries [17], obstetrical anal sphincter injury [18], smoking [19], menopausal status [9] and depression [20]. We also added variables with a significant association to anal incontinence symptoms at univariable analysis to the multivariable model.…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous other risk factors for anal incontinence, obesity frequently is correlated to the presence of anal incontinence in crosssectional studies [8][9][10][11]. However, previous studies focusing on the specific association between obesity and anal incontinence are few, limited by small population samples and lack of non-obese control subjects [12,13]. Thus, the relationship between obesity and anal incontinence remain unconfirmed in controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…10 Other studies have suggested higher intra-abdominal pressure chronically stresses the pelvic floor 22 and BMI is positively associated with lower urinary tract health conditions (eg, incontinence). 23 Also, overweight/obese people may be more likely to get screened because of more frequent health care provider use due to comorbid conditions associated with their weight. It is plausible that, given the very high prevalence of obesity among AI/ANs, 6,24 being overweight has become the norm.…”
Section: Discussionmentioning
confidence: 99%
“…There are also potential gender differences in the longer-term efficacy of bariatric surgery. For example, obesity is a known risk factor for several health conditions specific to and prevalent among women such as menstrual abnormalities, infertility 49 , and urinary incontinence 50 . It is hypothesized that menstrual abnormalities, fertility, urinary incontinence, and symptoms of polycystic ovarian diseases will improve following bariatric surgery.…”
Section: Gender Issuesmentioning
confidence: 99%